Nanoparticle-electrode impacts: the oxidation of copper nanoparticles has slow kinetics. - Haddou, B; Rees, N; Compton, R (2012)
The electrochemical oxidation of copper nanoparticles in aqueous solution was studied via their electrolysis upon impacting a carbon electrode held at a suitable anodic potential. The oxidations were found to be quantitative such that complete oxidation of the particle took place allowing their sizing. Experiments were performed in 1.0 M HNO(3) and in 1.0 M HNO(3)-0.1 M KCl. In the former case a two electron oxidation to Cu(2+) was seen at a formal potential of +0.11 V (vs. SCE). In the latter case two separate one-electron oxidations at -0.01 V and +0.26 V were seen. In addition, theoretical results were derived for the analysis of impact-charge vs. potential data for reversible and irreversible charge transfer kinetics for nanoparticle oxidation. This enabled the inference that overpotential is required for the oxidations and Butler-Volmer transfer coefficients to be determined. The latter are compared with literature data seen for macroscopic copper.